1997
DOI: 10.1111/j.1460-9568.1997.tb01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of ChAT lmmunoreactivity in Axotomized Rat Cholinergic Septal Neurons Despite Reduced NGF Receptor Expression

Abstract: Previous studies have suggested that target-derived nerve growth factor (NGF) is essential for the survival of cholinergic basal forebrain neurons. Thus, axotomy of septohippocampal neurons in adult rats resulting in the withdrawal of target-derived NGF caused a dramatic loss of choline acetyltransferase (ChAT)-immunoreactive neurons in the medial septum-diagonal band complex. We have recently shown that this loss of immunolabelled neurons does not indicate cell death, since many septohippocampal cholinergic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 79 publications
(75 reference statements)
2
16
1
Order By: Relevance
“…In line with this finding, our electron microscopic analysis revealed only very few microglial cells exhibiting signs of phagocytotic activity. These observations are in agreement with our previous studies, which had shown that the majority of septohippocampal projection neurons survive after axotomy but downregulate the synthesis of some cell type-specific markers in the early postlesional period (Peterson et al, 1990;Naumann et al, 1992bNaumann et al, , 1994Naumann et al, , 1997 Kermer et al, 1995;Haas et al, 1996;Hä ge et al, 1996). The presence of activated microglial cells containing myelin debris in the MS after short survival time can be explained, at least in part, by the degeneration of the small direct hippocamposeptal projection to the MS (Tóth and Freund, 1992) and by the degeneration of other hippocampal efferents passing through the septal region (Amaral and Witter, 1995).…”
Section: Postlesional Microglial Activation Varies With the Lesion Pasupporting
confidence: 94%
See 2 more Smart Citations
“…In line with this finding, our electron microscopic analysis revealed only very few microglial cells exhibiting signs of phagocytotic activity. These observations are in agreement with our previous studies, which had shown that the majority of septohippocampal projection neurons survive after axotomy but downregulate the synthesis of some cell type-specific markers in the early postlesional period (Peterson et al, 1990;Naumann et al, 1992bNaumann et al, , 1994Naumann et al, , 1997 Kermer et al, 1995;Haas et al, 1996;Hä ge et al, 1996). The presence of activated microglial cells containing myelin debris in the MS after short survival time can be explained, at least in part, by the degeneration of the small direct hippocamposeptal projection to the MS (Tóth and Freund, 1992) and by the degeneration of other hippocampal efferents passing through the septal region (Amaral and Witter, 1995).…”
Section: Postlesional Microglial Activation Varies With the Lesion Pasupporting
confidence: 94%
“…Beside the fact that these axotomized neurons are altered with respect to the expression of neurotrophin receptors (Naumann et al, 1997), we have no evidence for a second wave of neuronal degeneration as observed for motoneurons (Bowe et al, 1988(Bowe et al, , 1992. Even 18 months following ff-t, the longest survival time analyzed so far, the axotomized cholinergic and parvalbumin-containing projection neurons displayed fine structural characteristics of normal MS cells (Kermer et al, 1995;Frotscher et al, 1996).…”
Section: Does the Second Wave Of Microglial Activation Indicate A Latmentioning
confidence: 91%
See 1 more Smart Citation
“…These converging lines of evidence suggest that following a neurotoxic event, cholinergic neurons, in particular those that have nestin as a cofactor, do not immediately die, but rather enter an atrophic quiescent state in which they do not express the enzymes required to maintain cholinergic transmission. In contrast, a significant portion of cholinergic neurons (30–40%) can be rescued from a pathological state with timely and repeated exposure to NGF (Nagahara et al, 2009; Naumann et al, 1997; Tuszynski and Gage, 1995) or BDNF (Morse et al, 1993). It should be noted that this is the percentage of ChAT+ neurons within the basal forebrain that express nestin.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of 2-wks for the length of exercise exposure was chosen because this period is sufficient to reverse hippocampal-based cognitive deficits in several other models of cognitive dysfunction (Hall et al, 2014; van Praag et al, 2005). Given that cholinergic remodeling takes time (Gustilo et al, 1999; Naumann et al, 1997), we assessed the recovery of septohippocampal functioning at two time periods: shortly after exercise (24-hrs post exercise) and after an extended adaption period (2-wks post exercise). This design permits the detection of the critical period needed for exercise to modulate the cholinergic septohippocampal system.…”
Section: Introductionmentioning
confidence: 99%